A preliminary study of insect fauna on pig carcasses located in sugarcane in winter in southeastern Brazil - Gomes, L. [UNESP]; Gomes, G. [UNESP]; Desuo, I. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Minimum post-mortem intervals can be estimated based on analyses of the pattern of insect succession on a carcass. In order to successfully apply this approach, insect development rates must be considered with regard to local regional climatic conditions. This study is the first to analyse insect succession on carcasses decomposing in a sugarcane crop in Brazil. In all seasons, Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) and Cochliomyia macellaria (Fabricius) were frequent visitors during the fresh and bloated stages of decomposition, whereas Dermestes maculatus (De Geer) (Coleoptera: Dermistdae), Necrobia rufipes (De Geer) (Coleoptera: Cleridae) and Oxelytrum sp. (Coleoptera: Silphidae) were characteristic at the most advanced decomposition stages. The fact that climatic variations influence the occurrence of insect species and vegetation in the tropics may help to solve crimes through sampling of the local insect fauna, as may the fact that only certain groups of insects occur in specific regions of large countries like Brazil.
Keywords: Forensic entomology; insect succession; neotropics; sugarcane crop; São Paulo